Health Systems Response to Routine Maternal and Child Health Service Delivery Amidst COVID -19 Pandemic at Kanyama 1st Level Hospital - Lusaka District - Syakayuwa, Tandwa; Chansa, Regina (British Journal of Healthcare and Medical Research, 2022)
Aim: To ascertaining the health systems response to routine maternal and child health services amidst the COVID -19 pandemic at Kanyama 1st Level Hospital – Lusaka, Zambia. Method: A qualitative research study was conducted on Antenatal Clinic and Post Natal Clinic mothers as targets; Community Health Workers, Health Care Workers, and policy makers as key informants, utilizing five (5) Focused group discussion to reach saturation. Data was collected using topic guides and analyzed manually by transcribing and coding it. Sample size for participants were selected using simple random sampling on ANC/ PNC mothers, while the three categories of key informants were purposefully selected. The indirect effects of COVID-19 pandemic framework which mirrors the WHO six building blocks adopted from the Global Health Life Saving Tools was used to analyze the health system’s readiness amidst the COVID-19 pandemic at Kanyama 1st Level Hospital – Lusaka, Zambia. Results Findings were that the facility had challenges with regards to health workforce, supplies and equipment, which ultimately affected quality provision of maternal health services as outreach services were disrupted. Although the health facility responded well in providing alternative schedule to cope with the influx of mothers at the center from the closed outreach posts, the epidemic preparedness in responding to the epidemic was not up to the expected standards. Later, reduction in PNC and ANC attendance was noted, and home deliveries and deaths suddenly increased. The HCW, CHWs also had challenges ranging from lack of psychosocial support / Personal Protection Equipments, and inadequate training. In addition, frontline workers had inadequate knowledge on triaging a Covid-19 suspected pregnant mothers. Also findings such as lack of tracking system for follow up on mothers who missed appointments due to fear of contracting COVID -19; and essential drug stock out was noted during the pandemic. Monitoring and evaluation system was in place but irregular and not in tandem with prompt feedback that was required. On the other hand, the study results also revealed one positive aspect of ANC/PNC mothers having knowledge on the importance of maternal services despite fears for COVID – 19 , facility delivery, signs and symptoms of COVID -19 infections and preventive measures. However, the end users expressed myths on the transmission of the virus and the testing process. Conclusion: the research revealed lack of epidemic preparedness at Kanyama 1st level hospital that would allow the continuation of maternal and child health services amidst the COVID-19 outbreak. The facility had needed a timely and comprehensive health system response to the epidemic that is elaborate and specific to respond to all specifics of the health system in relation to maternal services verses COVID -19 which would have been the answer to this call.